2021
DOI: 10.1007/s42448-021-00074-w
|View full text |Cite|
|
Sign up to set email alerts
|

Adolescent Mother Maltreatment Perpetrators’ Past Experiences with Child Protective Services

Abstract: The experience of childhood maltreatment is associated with pregnancy during adolescence and increased risk for maltreating one’s own child or children. However, adolescent mothers who have been identified by child protective services (CPS) both as perpetrators and alleged victims carry a unique burden of trauma and are seldom the focus of retrospective studies. This study examines the extent to which adolescent mother perpetrators have prior experience with CPS as alleged victims and how their current perpetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Greater neglect is found in mothers under the age of 18 than in mothers between 18-21. Adolescent mothers who have experienced abuse and neglect are also at risk for the perpetuation of such behavior (aggressive, hostile conduct and abuse) with their infants, leading to intergenerational transmission of the trauma from mother to child [26]. From a psychodynamic perspective, it may be hypothesized that adolescents who have had adverse experiences see motherhood as a potential opportunity for redemption and/or reparation of emotional deprivation and interpersonal dysfunction they had in their multiproblematic family [90].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Greater neglect is found in mothers under the age of 18 than in mothers between 18-21. Adolescent mothers who have experienced abuse and neglect are also at risk for the perpetuation of such behavior (aggressive, hostile conduct and abuse) with their infants, leading to intergenerational transmission of the trauma from mother to child [26]. From a psychodynamic perspective, it may be hypothesized that adolescents who have had adverse experiences see motherhood as a potential opportunity for redemption and/or reparation of emotional deprivation and interpersonal dysfunction they had in their multiproblematic family [90].…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to an increase on the part of adolescent mothers in maltreatment of and hostile behavior towards the infant [24], with intergenerational transmission of traumatic experiences from mother to child [25]. The types of maltreatment which adolescent mothers alleged they had experienced during childhood were related to the type of maltreatment they perpetrated [26]. A recent study [26] reported that 62% of adolescent mothers who maltreated their children had prior experience with child protective services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation